2021
DOI: 10.1088/1755-1315/664/1/012054
|View full text |Cite
|
Sign up to set email alerts
|

Study of energy consumption in a wastewater treatment plant using logistic regression

Abstract: The aim of this paper is to predict the energy consumption of a wastewater treatment plant from Romania, taking into account the flowrate, concentration of BOD, TSS, COD and the energy consumption. For the mathematical model the logistic regression was applied. The input data used were from a waste treatment plant in Romania, for a period of 2 years 2015 and 2017, a total of random 403 dataset. The treatment technologies of WWTP consist of advanced biological treatment SBR (nitrification, denitrification, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…Bonescu et al [23] considered the logistic regression method (LRM). This approach involved the use of input variables such as flow rate and wastewater properties to predict the EC of a WWTP in Romania.…”
Section: Project Performance Prediction Modelsmentioning
confidence: 99%
“…Bonescu et al [23] considered the logistic regression method (LRM). This approach involved the use of input variables such as flow rate and wastewater properties to predict the EC of a WWTP in Romania.…”
Section: Project Performance Prediction Modelsmentioning
confidence: 99%
“…Excess sludge is thickened in the mechanical thickener (8) and mixed with the preliminary sludge before being sent to the mesophilic fermentation chamber (9). The fermented sludge is dewatered in the decantation centrifuge (10). The sludge dewatering process is assisted by fl occulant.…”
Section: Characteristics Of the Wwtp 1 -2mentioning
confidence: 99%
“…al. found that the concentration of pollutants among others total suspended solids (TSS) in the sewage was a signifi cant predictor of electricity consumption in the downstream biological treatment process 10 . Research by Mininni et.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results demonstrated that in terms of the Root mean squared error (RMSE) and Mean Absolute Error (MAE) values, the GBU had the lowest values in the test phase, 33.9 and 26.9, respectively. In [12], logistic regression was employed to estimate the energy consumption of a WWTP. The effectiveness of this approach has been assessed using data with 403 records collected from Romania between 2015 and 2017.…”
Section: Machine Learning Has Recently Been Explored To Controlmentioning
confidence: 99%